1993
DOI: 10.1128/jb.175.1.7-11.1993
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and recycling of the murein sacculus in oligopeptide permease-negative strains of Escherichia coli: indirect evidence for an alternative permease system and for a monolayered sacculus

Abstract: Turnover of murein in oligopeptide permease-negative Escherichia coli cells appeared to be minimal or nonexistent. In one strain in which it was possible to measure turnover during the first generation of chase, it was found that the rate of turnover was constant throughout a chase of three generations. This result suggests that an "inside-to-outside" mode of growth of the sacculus does not occur in E. coli. Turnover, though minimal, was significantly higher from cells labeled uniformly than from cells labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…However, on comparing and integrating his results with those of Labischinski et al (1991), Park (1993) also suggested speculatively that, while lateral wall PG may be monolayered, septal wall PG (and poles) may be triplelayered. Now, for the first time, biochemical evidence supporting this conclusion has been found in E. coli.…”
mentioning
confidence: 77%
“…However, on comparing and integrating his results with those of Labischinski et al (1991), Park (1993) also suggested speculatively that, while lateral wall PG may be monolayered, septal wall PG (and poles) may be triplelayered. Now, for the first time, biochemical evidence supporting this conclusion has been found in E. coli.…”
mentioning
confidence: 77%
“…Their physiological functions are still uncertain, although they have been implicated in autolysis and/or peptidoglycan recycling (Parquet et al, 1983;Kitano et al, 1986;Goodell and Higgins, 1987;Shockman and HĂś ltje, 1994). The relevance of AmiA and AmiB in peptidoglycan recycling has been questioned by the recent finding in E. coli of a muropeptide-permease, AmpG, and a cytosolic N-acetyl-muramyl-L-alanine amidase, AmpD, which apparently mediate the main recycling pathway (Park, 1993;HĂś ltje et al, 1994;Jacobs et al, 1994;. Incidentally, a DNA fragment with extensive homology to E. coli ampD has also been identified in S. typhimurium (Hughes et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Cells release PG during growth (72,73), but the mechanism of PG turnover is not clear. It was proposed in the 'three-for-one' model that PG turnover is a result of a PG remodeling mechanism that replaces one existing strand with three new strands (12).…”
Section: Discussionmentioning
confidence: 99%